2017
DOI: 10.21149/7735
|View full text |Cite
|
Sign up to set email alerts
|

Exposición a la publicidad de tabaco y consumo de tabaco en adolescentes en América del Sur

Abstract: Objetivo. Este estudio evalúa la relación estadística entre la exposición a la publicidad de tabaco y el tabaquismo en los adolescentes de América del Sur. Material y métodos. Usando datos de la Encuesta Mundial de Tabaquismo en Jóvenes (GYTS) se estudiaron los niveles de exposición a nivel de escuela, ante distintos tipos de publicidad, además se evaluaron los comportamientos asociados al tabaquismo durante la experimentación y consumo. La muestra total fue de 134 073 jóvenes de Argentina, Bolivia, Chile, Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
1
9
0
1
Order By: Relevance
“…The obtained results in previous researches must be utilized as primaries elements to design health promotion strategies to contribute to reduce and eliminate the tobacco consumption as main cause of the smoking economic impact over the Public Health services. 23 These estrategies must be valuated constantly. This means that all previous roles must be present at same time for the health services dispenser.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…The obtained results in previous researches must be utilized as primaries elements to design health promotion strategies to contribute to reduce and eliminate the tobacco consumption as main cause of the smoking economic impact over the Public Health services. 23 These estrategies must be valuated constantly. This means that all previous roles must be present at same time for the health services dispenser.…”
Section: Globalize Your Researchmentioning
confidence: 99%
“…Another study based on data from the Global Youth Tobacco Survey found that exposure to tobacco marketing is positively and significantly associated with both smoking intensity and the probability of experimenting with tobacco (9). The ENS 2017 results for the younger age groups could provide fresh and robust evidence to support this association, as marketing of tobacco products in Chile was severely curtailed after enactment of Law 20.660.…”
Section: The Effect Of Public Policymentioning
confidence: 99%
“…A 2011 Cochrane meta-analysis evaluated 19 longitudinal studies, mainly from the US, in which 18 studies reported that non-smoking adolescents exposed to TAPS were more likely to become smokers 8 . Another study in adolescents from South America that used the GYTS databases from 1999 to 2008 found a positive association between exposure to tobacco advertising (television, billboards, and events) and experimentation with conventional cigarettes in non-smokers and an increased intensity of habitual consumption in smokers 9 . On the other hand, in 2019, the tobacco industry in the US invested approximately 22.5 million dollars per day in the promotion of conventional cigarettes, which was demonstrated to be effective in influencing adolescents to initiate tobacco consumption 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study in adolescents from South America that used the GYTS databases from 1999 to 2008 found a positive association between exposure to tobacco advertising (television, billboards, and events) and experimentation with conventional cigarettes in non-smokers and an increased intensity of habitual consumption in smokers 9 . On the other hand, in 2019, the tobacco industry in the US invested approximately 22.5 million dollars per day in the promotion of conventional cigarettes, which was demonstrated to be effective in influencing adolescents to initiate tobacco consumption 8 , 9 . For this reason and given that adolescents are part of the target audience of the tobacco industry, evidence is required to strengthen decision-making on anti-smoking public health strategies, mainly aimed at reducing exposure to advertising on its consumption.…”
Section: Introductionmentioning
confidence: 99%